Farmers' Knowledge and Skills in Shallot Farming in Pucang Simo Village, Jombang Regency - Ari Dwi Putra; Yessita Puspaningrum; Miftachul Chusnah (AGARICUS: Advances Agriculture Science & Farming, 2026)
The ability of farmers to apply efficient and sustainable agricultural techniques depends critically on their knowledge and abilities. The purpose of this study was to evaluate shallot farmers' knowledge and abilities in Pucang Simo Village, Jombang, Indonesia. Thirty shallot farmers were chosen from a population of 150 farmers to participate in a descriptive quantitative study. Questionnaires, interviews, observations, and documentation were used to gather data.The research instrument was tested using Pearson's Product-Moment validity test and Cronbach's Alpha reliability test. Of the 30 questionnaire items, 23 were found to be valid (r-count > 0.374), while the instrument demonstrated high reliability with a Cronbach's Alpha coefficient of 0.915. Descriptive statistical analysis was used to determine the mean scores of farmers' knowledge and skills based on their educational level. The results showed that farmers generally possessed high levels of knowledge and skills across all educational groups. Mean knowledge scores ranged from 2.48 to 3.00, while mean skill scores ranged from 2.00 to 3.00 on a three-point Likert scale. Although most respondents had completed only elementary education, they demonstrated a high level of competence in implementing shallot farming practices. These findings suggest that practical farming experience and continuous learning may help strengthen farmers' competencies regardless of their formal educational background. The study provides useful insights for agricultural extension programs aimed at improving farmers' knowledge and technical skills to support sustainable shallot farming.